Arthroplasty implant registries over the past five decades: Development, current, and future impact. Issue 9 (24th May 2018) - Malchau, Henrik; Garellick, Göran; Berry, Daniel; Harris, William H.; Robertson, Otto; Kärrlholm, Johan; Lewallen, David; Bragdon, Charles R.; Lidgren, Lars; Herberts, Peter
ABSTRACT: Local, regional, and national registries have played an important role in the development of hip and knee arthroplasty and the treatment of patients with various maladies of these joints. Four arthroplasty registries stand out as leading forces behind the drive to popularize the use of registries and pursue the concept of evidence based medicine. The Mayo registry, started by Mark Coventry, is recognized as the oldest continuing registry for arthroplasty. The Harris Registry at Massachusetts General Hospital, along with the Mayo Registry, has greatly contributed to the advancement of arthroplasty surgery and have served an important role of identifying poorly performing implants and techniques in the United States. The Swedish Knee Arthroplasty Registry is the oldest national registry dedicated to joint arthroplasty and along with the Swedish Hip Arthroplasty Registry have established the infrastructure, analysis and reporting mechanisms, and leadership that has enabled other countries to subsequently develop national registries around the world. As more countries have adopted the concept of national registries, a new area of research is possible by pooling the resources of large registries as is now occurring with the Nordic countries. Several international organizations have been formed to promote future collaboration and develop international standards. The process of globalization of registries is a result of continued efforts over the past 50 years in improving and disseminating the knowledge gained from the early registries. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2319–2330, 2018.